MAGNESIUM METABOLISM AND CLINICAL CHARACTERISTICS OF PATIENTS WITH CHRONIC ISCHEMIC HEART DISEASE - A. V. Yezhov; L. T. Pimenov; M. A. Makarova; T. V. Savelyev (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study relationship of the clinical state and cardiac functional parameters with magnesium metabolism indices in patients with chronic ischemic heart disease (IHD).Material and methods. Patients with stable angina pectoris, II-III class (n=480) were involved into the study. Evaluation of the following items was performed: disease course, anxiodepressive syndrome intensity, exercise tolerance, blood and urine electrolyte profile, systolic and diastolic left ventricle function, endothelium-dependent and endotheliumnondependent vasodilatation, i/v magnesium load test, Holter electrocardiogram monitoring.Results. High prevalence of systemic magnesium deficiency (17.9 and 37.5% according to serum and erythrocyte levels, respectively) was found in IHD patients. Severity of magnesium deficiency in IHD patients depended on duration of disease, experience of myocardial infarction, myocardial ischemia seriousness, disorders of endothelium vasodilating function and left ventricle diastolic function, severity of concomitant anxiety. Exercise tests were changed in IHD patients with magnesium deficiency.Conclusion. The study data let to consider that magnesium deficiency involves into the IHD pathogenesis.